Riding a dream - Azizi Hashim (Shakesport, 2011)
Captain Azizi Hashim, a pilot with three other Malaysians of different races who had no previous experience, led a motorcycling expedition across continents by land on the 650cc kawasaki versys within 62 days, crossing 18 countries from Kuala Lumpur to London successfully.